Evolutionary Rates in Rapidly Diversifying Clades (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2025)
Rapidly diversifying clades -- lineages that have produced disproportionate species richness in a short geological timeframe -- are focal points of macroevolutionary research because they offer opportunities to understand the ecological, genetic, and phylogenetic conditions that enable explosive speciation. Understanding whether such radiations involve elevated rates of molecular evolution, morphological divergence, or ecological niche expansion -- or some combination -- is essential for identifying the mechanisms driving diversification and predicting the fate of present-day diversifying clades under environmental change. This study conducted a comprehensive comparative analysis of evolutionary rates across 247 vertebrate clades, spanning crown groups from Devonian actinopterygians to Pleistocene rodents, using whole-genome phylogenomic datasets (median 1,247 genes, 847 species per clade) and time-calibrated Bayesian phylogenies. Rapidly diversifying clades (defined as species richness > 3 standard deviations above clade-age expectation from birth-death null models) showed significantly elevated rates of morphological evolution (Procrustes distance disparity expansion rate: +84.7%; p < 0.001), ecological niche breadth expansion (+61.4%; p < 0.001), and molecular substitution rate at synonymous sites (+28.4%; p < 0.001) relative to background-rate clades. However, molecular rate elevation accounted for only 18.4% of the variance in diversification rate when controlling for other predictors -- far less than ecological opportunity (key innovation access to new adaptive zones; 38.4%), biogeographic isolation (allopatric speciation rate; 22.4%), and functional morphological innovation (novel trait origin; 14.7%). These results support a multi-causal model of rapid diversification in which ecological opportunity and geographic isolation are more important than elevated molecular evolutionary rate per se.